Prostaglandin F2α in vitro can affect basic inflammatory parameters of mesenchymal stem cells and slight modulating some of their immunomodulatory properties. (December 2020) - Santos, Andressa Cristina Antunes; Sartori, Talita; Borelli, Primavera; Fock, Ricardo Ambrosio
Highlights: PGF2α increases proliferation tax of mesenchymal stem cells. PGF2α modulates the phosphorylation of NFκB transcription factor of mesenchymal stem cells. PGF2α reduces the IL-1β and GM-CSF production by mesenchymal stem cells. Mesenchymal stem cells stimulated with PGF2α were able to increase the lymphocytes' IL-10 production. ABSTRACT: In the last decade, mesenchymal stem cells (MSCs) have been gaining attention due their ability to influence the function of other cells as well as modulate the inflammatory response. This occurs via their immunomodulatory functions,   acting through direct cell-cell interaction or by releasing a broad spectrum of bioactive factors such as cytokines and growth factors. In addition, prostaglandins are arachidonic acid metabolites that play a key role in the generation and modulation of the inflammatory response. Among the bioactive prostaglandins, PGF2α  is able to stimulate cell proliferation as well as act to inhibit progenitor cell differentiation, but no information about this prostaglandin's action on the immunoregulatory function of MSCs has been reported. In this study we evaluate important aspects of the influence of PGF2α analog (17-phenyl-trinor PGF2α ), which is a potent prostaglandin FP receptor agonist, on some mechanisms that control the main functions of MSCs. C3H10T1/2, a mesenchymal stem cell linage, was stimulated with PGF2α under inflammatory conditions trigged by LPS in order to investigate PGF2α inflammatory parameters as well as its ability to immunoregulate macrophages and lymphocytes. PGF2α has the ability to increase proliferation tax without altering the cell viability of LPS-stimulated MSCs, while also diminishing the phosphorylation of NFκB transcription factor leading to attenuation of IL-1β and GM-CSF production. Additionally, MSC-s conditioned media from cells stimulated with PGF2α was able to increase the lymphocytes' IL-10 production. Overall, this study implied that PGF2α are able to modify some properties of MSCs.